Prehistoric Cultural Change at Kitselas Canyon - Coupland, Gary Graham, 1953- (Book collections on Project MUSE., 1988)
A study which investigates prehistoric transition from egalitarian to ranked social structure at Kitselas Canyon, Skeena River, British Columbia.